Analysis of Shear Wall Placement Configuration on Building Structure Behavior - Hidayati, Nurul; Zarkasi, Ahmad; Hariyadi, Hariyadi; Sahlinda, Ranni (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2025)
Lombok Island is one of the earthquake-prone areas, located between two earthquake generators. Based on these conditions, it is expected that construction in earthquake-prone areas can meet the standards. Shear walls are one of the earthquake-resistant structural systems used to resist lateral forces. Three alternative shear wall shapes will be analyzed using the numerical method: the L, I, and T shapes. The types of loads to be analyzed are dead loads, live loads, and earthquakes. Drawing from the findings of the conducted analysis, it is discovered that the most effective shear wall position in resisting lateral forces is the shear wall located at the corner of the building, based on the values of the drift that occur in the x and y directions. In addition, increasing the number of shear walls can reduce the internal forces that structural components experience. The optimum drift value is obtained from alternative 1, the L-shaped shear wall (elbow), with a drift value of 0.000495 mm in the x direction and 0.000883 in the y direction.